Eksistensi Batik Tulis Sebagai Identitas Kabupaten Pamekasan - Rachman Hakim; Anne Rufaidah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2021)
Pamekasan handmade batik is a work of art that must be preserved and its existence is not forgotten. The purpose of this study was to measure the knowledge of the Pamekasan community regarding the types of handmade batik in Pamekasan Regency, the marketing of Pamekasan handmade batik, and to prove the extent to which the Pamekasan community still uses Pamekasan handmade batik as a form of cultural preservation. The method used is qualitative research. The results show that batik marketing is not only through selling in the market but also being sold online, either using Facebook, Instagram or other social media. In addition, most Pamekasan people do not know the types of Pamekasan batik motifs. The existence of Pamekasan batik is still very well maintained, many Pamekasan people still use Pamekasan batik in their daily life or when attending certain events. However, the batik used is stamped batik, not handmade batik.